The Palgrave International Handbook of School Discipline, Surveillance, and Social Control (Springer International Publishing, 2018)
Truly international in scope, this Handbook focuses on approaches to discipline, surveillance and social control from around the world, critically examining the strategies and practices schools employ to monitor students and control their behavior. Bringing together leading scholars from a range of disciplinary backgrounds, the chapters scrutinize, analyze and compare schools' practices across the globe, providing a critical review of existing evidence, debates and understandings, while looking forward to address emerging important questions and key policy issues. The chapters are divided into four sections. Part 1 offers accounts of international trends in school discipline, surveillance and punishment; Part 2 examines the merging of school strategies with criminal justice practices; Part 3 focuses on developments in school technological surveillance; and Part 4 concludes by discussing restorative and balanced approaches to school discipline and behavior management. As the first Handbook to draw together these multiple themes into one text, and the first international comparative collection on school discipline, surveillance and social control, it will appeal to scholars across a range of fields including sociology, education, criminology, critical security studies and psychology, providing a unique, timely, and indispensable resource for undergraduate educators and researchers.